Writing Motivation in Educational Contexts: A Systematic Review of Research Trends and Future Directions (2001–2025) - Ikram, Maryam; Wang, Tianqiao; Sun, Cuimei (Forum for Linguistic Studies, 2025)
This research aims to provide researchers with a comprehensive literature review while demonstrating how writing motivation in educational institutions has led to the development of viable research avenues for future analysis and research. This systematic literature review emphasizes the value of incorporating students’perspectives. It draws on empirical studies published between 2001 and 2025, sourced from the Scopus database. Out of 73 initially identified studies, 30 met the inclusion criteria and were subjected to qualitative analysis. This review concludes with a comprehensive depiction of how writing motivation is being studied in educational contexts. The dominance of quantitative research methods highlights a gap in capturing the multifaceted nature of motivation, whereas the presence of qualitative studies opens doors to innovative methodological practices. The broad geographical spread of studies, particularly within Europe, demonstrates the worldwide importance of this topic. These findings contribute to our understanding of current research trends and suggest meaningful directions for future studies to enhance writing instruction through more adaptable and context-aware approaches. This study is the first to systematically analyse and review existing research on writing motivation alongside meta-literature reviews. It offers researchers a clear overview of the field’s evolution and emerging trends. Additionally, the findings highlight potential directions for future studies and serve as a useful foundation for further scholarly exploration.